Role of Fatty-acid Synthesis in Dendritic Cell Generation and Function - Rehman, Adeel (2013)
Dendritic cells (DC) are professional antigen presenting cells that regulate innate and adaptive immunity. The role of fatty-acid synthesis in DC development and function is uncertain. We found that blockade of fatty-acid synthesis markedly decreases dendropoiesis in the liver and in primary and secondary lymphoid organs in mice. Human DC development from PBMC precursors was also diminished by blockade of fatty-acid synthesis. This was associated with higher rates of apoptosis in precursor cells and increased expression of Cleaved Caspase 3 and BCL-xL, and down-regulation of Cyclin B1. Further, blockade of fatty-acid synthesis decreased DC expression of MHCII, ICAM-1, B7-1, B7-2 but increased their production of selected pro-inflammatory cytokines including IL-12 and MCP-1. Accordingly, inhibition of fatty-acid synthesis enhanced DC capacityto activate allogeneic as well as antigen-restricted CD4(+) and CD8(+) T cells and induce CTL responses. Further, blockade of fatty-acid synthesis increased DC expression of Notch ligands and enhanced their ability to activate NK cell immune-phenotype and IFN-γ production. Since endoplasmic reticular (ER)-stress can augment the immunogenic function of APC, we postulated that this may account for the higher DC immunogenicity. We found that inhibition of fatty-acid synthesis resulted in elevated expression of numerous markers of ER stress in humans and mice and was associated with increased MAP kinase and Akt signaling. Further, lowering ER-stress by 4-phenylbutyrate mitigated the enhanced immune-stimulation associated with fatty-acid synthesis blockade. Our findings elucidate the role of fatty-acid synthesis in DC development and function and have implications to the design of DC vaccines for immunotherapy.